2019
DOI: 10.18280/ts.360108
|View full text |Cite
|
Sign up to set email alerts
|

Outage Probability Analysis of MIMO-OSTBC Relaying Network Over Nakagami-m Fading Channel Conditions

Abstract: The objective of this study is to examine the outage probability (OP) performance of the multiple-input multiple-output (MIMO) cooperative communication system over Nakagamim fading channel conditions. Source node transmits orthogonal space time block code (OSTBC) codeword to the relay & destination node and maximal ratio combiner (MRC) is used for the decoding purpose at the destination node. A mathematical framework is developed for the analysis of diversity order (DO) of the system. The closed form expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…In order to keep the data rate of the SR fading link same as that of the RD fading link, we herein propose to use the same Alamouti orthogonal space time block code (OSTBC) at the source and relay, respectively. This also means that, == SR N N N [9][10][11][12]. Let , ( corresponding to the MIMO STBC codeword transmission from the source can be written as [9], [10], [17],…”
Section: System Model Of Mimo Stbc S-df Cooperative Communication Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to keep the data rate of the SR fading link same as that of the RD fading link, we herein propose to use the same Alamouti orthogonal space time block code (OSTBC) at the source and relay, respectively. This also means that, == SR N N N [9][10][11][12]. Let , ( corresponding to the MIMO STBC codeword transmission from the source can be written as [9], [10], [17],…”
Section: System Model Of Mimo Stbc S-df Cooperative Communication Systemmentioning
confidence: 99%
“…However, if the channel between the source and the relay suffer a severe fading and the SNR falls below the threshold; the relay remains idle. In the past, some significant works have been done by the researchers on S-DF based cooperative communication systems [9][10][11]. Further, it is observed that the performance of S-DF protocol-based system can be improved with the use of multiple parallel relay nodes which helps in achieving diversity gain.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Time-varying channels will introduce inter-carrier interference (ICI), disrupt sub-carrier orthogonality and degrade system performance [4,5]. The issue makes it much more difficult if multiple-input multiple-output (MIMO) construction is approve because, on every subcarrier on the particular beneficiary, signal along with ICI as of any senders are mixed up [6].…”
mentioning
confidence: 99%